A escolha de livros de literatura infantil por professoras da educação infantil - Dayenne de Souza Bassut Pereira (2022)
Although children's literature is a field of study with a significant number of productions, there are few studies that deal with book choices by preschool teachers. How is the selection of books that are part of the schools' collections and each kindergarten class carried out? Who participates in this selection? What role do the teachers play in this selection process? If they participate in the selection process, what criteria do they use to compose children's book collections for kindergartens and preschools? This study aimed to learn and understand how preschool teachers choose literature books to compose their collections and/or to develop learning situations with children under six years of age, in the daycare centers or preschools where they work. The research included a brief analysis of the work with literature in Children's Education and how it is addressed in official documents, such as the National Curricular Guidelines for Children's Education and the Common National Curricular Base, in addition to discussing two concepts that were fundamental to the data analysis: Bibliodiversity and quality in children's literature. This quanti-qualitative research was carried out through a 63-question questionnaire sent electronically to 87 teachers working in Municipal Schools of Early Childhood Education in Belo Horizonte who participated in the course Reading and Writing in Early Childhood Education. The results showed that half of the respondents said they had studied subjects on children's literature during their initial training and participated in processes to choose books that are worked with and/or read to the children in their classes. Regarding the criteria for choosing books, most of the teachers prefer books that have interesting themes, strong and vivid colors, attractive covers, adequate font size, and that enable the linguistic development of children. Although it is not possible to conclude that these criteria, when analyzed in isolation, determine an inadequate form of choice, it is noteworthy that other criteria related to the aesthetic aspects of the books are preferred.